Extremophiles from biology to biotechnology - Durvasula, Ravi; Subba Rao, D. V. (Boca Raton, FL CRC Press, Taylor & Francis Group, 2018)
Extremophiles are nature’s ultimate survivors, thriving in environments ranging from the frozen Antarctic to abyssal hot hydrothermal vents. Their lifeforms span bacteria to fishes, and are categorized as halophiles from hypersaline environments, acidophiles from acidic waters, psychrophiles from cold habitats, and thermophiles from warm waters. Extremophiles: From Biology to Biotechnology comprehensively covers the basic biology, physiology, habitats, secondary metabolites for bioprospecting, and biotechnology of these extreme survivors. The chapters focus on the novel genetic and biochemical traits that lend these organisms to biotechnological applications.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Extreme environments -- Microbiology; Extreme environments -- Biotechnology